Das thema 'sprache' in den werken Bachmanns, Handkes und Wieners - Strauss, Werner (German Language and Literature, 2024)
This study looks at the issue of language as a problematic means of portraying reality; an issue which characterized much of the work of post 1960 Austrian authors. The study concentrates on three authors, namely Ingeborg Bachmann, Peter Handke and Oswald Wiener. These three authors have been selected because, although all three draw on a common philosophical heritage, they have developed very different approaches to the problem of language in their works and because each author is representative of a particular period in the history of Austrian literature: Bachmann belonging to the group of writers associated with Paul Celan, Handke being part of the Graz group and Wiener as a member of the Vienna group The study commences by looking at the Austrian tradition of language scepticism, and considerable attention is given to the work of Karl Kraus, Fritz Mauthner and Ludwig Wittgenstein whose theories had a profound influence on all three authors. Each of the three writers chosen for this study is then considered separately. Attention is given to the background of each writer and to the influence of contemporary philosophical thought on his or her work. This is followed by an in-depth examination of selected works to determine how the writer concerned has approached the issue of language as a problematic means of communication. In conclusion the study compares and contrasts these different approaches to language and focuses on the issues emphasised by each author: Bachmann's view of how language functions as a constraint on female identity, Handke's view of the influence of language on society and Wiener's view of language as a means of manipulating the media and therefore society as a whole.